2012
DOI: 10.1103/physrevb.85.155319
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical properties of single site-controlled InGaAsN quantum wires grown on prepatterned GaAs substrates

Abstract: The properties of single site-controlled InGaAsN quantum wires (QWRs)-both untreated and irradiated with atomic hydrogen-are probed by micro-magnetophotoluminescence spectroscopy. The strong anisotropy of the diamagnetic shift measured for different orientations of the applied magnetic field confirms the one-dimensional nature of the QWR carrier wave function. In addition, the strain reduction associated with N incorporation is found to promote a larger indium intake in the QWR, enabling the realization of sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The extent of such Hinduced blueshift is consistent with an initial N concentration of $1% in the wires. 24 Moreover, the energy position ($1.11 eV) of the QWR peak in the hydrogenated InGaAsN sample [labeled as InGaAsN:H in Fig. 1(c)] suggests an In concentration of at least $40%, considerably higher than the 25%-30% estimated for a reference InGaAs QWR sample in Refs.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…The extent of such Hinduced blueshift is consistent with an initial N concentration of $1% in the wires. 24 Moreover, the energy position ($1.11 eV) of the QWR peak in the hydrogenated InGaAsN sample [labeled as InGaAsN:H in Fig. 1(c)] suggests an In concentration of at least $40%, considerably higher than the 25%-30% estimated for a reference InGaAs QWR sample in Refs.…”
mentioning
confidence: 80%
“…Recently, this method was paired to the large band-gap bowing typical of dilute-nitride materials 22 to grow high-quality InGaAsN QWRs that emit at $1.3 lm at room temperature and are thus naturally suited for the integration with nanophotonic devices operating in the telecommunications window. 23 Shortly afterwards, Felici et al 24 confirmed the 1D character of the carrier wave function in InGaAsN V-groove QWRs, by measuring the anisotropy of the diamagnetic shift of the QWR emission for different orientations of the applied magnetic field. 19 In the same work, the well-known capability of hydrogen to passivate nitrogen impurities in III-N-V alloys [25][26][27] was exploited to selectively "turn off" the effects of N incorporation by H irradiation, thus providing a way to separately estimate the concentration of N ($1%) and In ($40%) in the QWRs, as well as the effective wire thickness and width (both $10-15 nm).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…As discussed in Ref. [17], the one-dimensional nature of the QWR carrier wave function results in a strong anisotropy of the energy shift of the emission of InGaAsN Vgroove QWRs for different orientations of B (see Fig. 2), which can be effectively modeled by approximating the confinement in the QWR with an anisotropic parabolic potential [18].…”
Section: Introductionmentioning
confidence: 99%